Role of Wnt Signaling During In-Vitro Bovine Blastocyst Development and Maturation in Synergism with PPARδ Signaling - Tabinda Sidrat; Abdul Aziz Khan; Muhammad Idrees; Myeong-Don Joo; Lianguang Xu; Kyeong-Lim Lee; Il-Keun Kong (Cells, 2020)
Wnt/β-catenin signaling plays vital role in the regulation of cellular proliferation, migration, stem cells cell renewal and genetic stability. This pathway is crucial during the early developmental process; however, the distinct role of Wnt/β-catenin signaling during pre-implantation period of bovine embryonic development is obscure. Here, we evaluated the critical role of Wnt/β-catenin pathway in the regulation of bovine blastocyst (BL) development and hatching. 6 bromoindurbin-3’oxime (6-Bio) was used to stimulate the Wnt signaling. Treatment with 6-Bio induced the expression of peroxisome proliferator-activated receptor-delta (PPARδ). Interestingly, the PPARδ co-localized with β-catenin and form a complex with TCF/LEF transcription factor. This complex potentiated the expression of several Wnt directed genes, which regulate early embryonic development. Inhibition of PPARδ with selective inhibitor 4-chloro-N-(2-{[5-trifluoromethyl]-2-pyridyl]sulfonyl}ethyl)benzamide (Gsk3787) severely perturbed the BL formation and hatching. The addition of Wnt agonist successfully rescued the BL formation and hatching ability. Importantly, the activation of PPARδ expression by Wnt stimulation enhanced cell proliferation and fatty acid oxidation (FAO) metabolism to improve BL development and hatching. In conclusion, our study provides the evidence that Wnt induced PPARδ expression co-localizes with β-catenin and is a likely candidate of canonical Wnt pathway for the regulation of bovine embryonic development.